2015
DOI: 10.1007/s10763-015-9639-0
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Study of Finland and Chile: the Culture-Dependent Significance of the Individual and Interindividual Levels of the Mathematics-Related Affect

Abstract: Mathematics-related affect is established regarding both individual and interindividual levels. However, the interaction between the levels has not been elaborated. Furthermore, it is known that people may draw either from intrinsic or extrinsic experiences to construct their identities depending on their cultural environment. Thus, affective individual and interindividual levels seem to interact with culture. In this study we focus on the significance of and the interaction between the individual and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…These limitations suggest a possible next step in research, namely to conduct a study with a larger data sample in a wider variety of settings (e.g., federal states or countries) and using alternative sampling strategies (e.g., maximum variation sampling, probability sampling), so that a researcher could create a more thorough description of the perceptions students have of the emotional classroom climate in geometry lessons, which can then be generalizable to a population. In addition, drawings from entire classrooms across different grades and schools may provide a more holistic insight into the collective emotional climate in primary grade geometry lessons as was done in the work by Laine et al (2013Laine et al ( , 2015Laine et al ( , 2020 and Tuohilampi et al (2016). This would, in addition, allow for comparisons between different grades and schools.…”
Section: Limitations Of the Study And Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These limitations suggest a possible next step in research, namely to conduct a study with a larger data sample in a wider variety of settings (e.g., federal states or countries) and using alternative sampling strategies (e.g., maximum variation sampling, probability sampling), so that a researcher could create a more thorough description of the perceptions students have of the emotional classroom climate in geometry lessons, which can then be generalizable to a population. In addition, drawings from entire classrooms across different grades and schools may provide a more holistic insight into the collective emotional climate in primary grade geometry lessons as was done in the work by Laine et al (2013Laine et al ( , 2015Laine et al ( , 2020 and Tuohilampi et al (2016). This would, in addition, allow for comparisons between different grades and schools.…”
Section: Limitations Of the Study And Future Research Directionsmentioning
confidence: 99%
“…Although numerous studies researching emotions employed methods such as interviews, observations, and questionnaires (e.g., Reindl & Hascher, 2013;Schmude, 2005), in the last decade, there has been an increase in studies on emotions and emotional classroom climate using visual research methods, such as drawings (e.g., Dahlgren Johansson & Sumpter, 2010;Glasnović Gracin & Kuzle, 2018;Laine et al, 2013Laine et al, , 2015Laine et al, , 2020Tuohilampi et al, 2016). These studies have shown that children's drawings have great potential to provide a thorough insight into different aspects of classroom climate in school mathematics.…”
Section: Emotional Classroom Climate Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…INTRODUÇÃO Leitura e matemática são eixos centrais do currículo escolar e o papel destas habilidades nas sociedades tecnológicas modernas é fundamental (Beck et al, 2016). Nas últimas décadas, as preocupações com o declínio do interesse pelo estudo da matemática e a baixa compreensão em leitura das crianças foram expressas em diferentes medidas padronizadas de avaliação educacional (Kennedy;Lyons;Quinn, 2014;Tuohilampi et al 2014).…”
unclassified